La Transformation Des Syntagmes Nominaux Des Panneaux Routiers En France - Pratiwi, Ajeng Putri; Purwani, Neli (Didacticofrancia: Journal Didactique du FLE, 2020)
La transformation d'un syntagme nominal en phrase canonique est l'une des faÃƒÂ§ons de clarifier le sens des panneaux routiers pour les ÃƒÂ©tudiants de second semestre. Le but de cette recherche est de transformer les syntagmes nominaux du livre Ã¢â‚¬Å“Le Code de la Route 2019Ã¢â‚¬Â en phrases canoniques afin d'en clarifier la signification pour quÃ¢â‚¬â„¢il soit compris par les ÃƒÂ©tudiants de second semestre. Cette recherche a ÃƒÂ©tÃƒÂ© menÃƒÂ©e selon la mÃƒÂ©thode descriptive qualitative, et les donnÃƒÂ©es sont collectÃƒÂ©s par la mÃƒÂ©thode de documentation. AprÃƒÂ¨s l'analyse des donnÃƒÂ©es, le processus de transformation qui est appliquÃƒÂ© sont: addition; subtitution et addition; addition et suppression; et subtitution, addition, et permutation. Le type de transformation le plus appliquÃƒÂ© est lÃ¢â‚¬â„¢addition. Dans ce cas, si l'on suit le principe de phrase ÃƒÂ©conomique (SN), ce type de phrase entrave la comprÃƒÂ©hension. Donc, il est necessaire de reformuler en phrase canonique qui contient des ÃƒÂ©lÃƒÂ©ments de phrase plus detailÃƒÂ©s The transformation of a nominal phrase into a canonical sentence is one of the ways to clarify the meaning of road signs for second semester students. The aim of this research is to transform the nominal syntagms of the book Ã¢â‚¬Å“Le Code de la Route 2019Ã¢â‚¬Â into canonical sentences in order to clarify their meaning to be understood by second semester students. This research was conducted according to the qualitative descriptive method, and the data are collected by the documentation method. After the data analysis, the transformation process that is applied are: addition; subtitution and addition; addition and deletion; and subtitution, addition, and permutation. The most applied type of transformation is addition. In this case, if we follow the principle of economic sentence (SN), this type of sentence hinders understanding. Therefore, it is necessary to reformulate into a canonical sentence which contains more detailed sentence elements.